1998
DOI: 10.1016/s0735-1097(98)00359-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac death and stored electrograms in patients with third-generation implantable cardioverter-defibrillators

Abstract: Only 37 patients (31%) who died after placement of an ICD had a stored EGM within 1 h of the time of death, suggesting that the majority of deaths (69%) were not the immediate result of a tachyarrhythmia. When EGMs were recorded, they were wide in 89% of patients. These wide EGMs most likely represent intracardiac recordings of electromechanical dissociation. Thus, of the 119 deaths, 112 (94%) were not the immediate result of a tachyarrhythmia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…A postmortem interrogation of implantable defibrillators in 83 patients with HF found that the prime mode of death was not an arrhythmia in 69% of the patients, with 16.9% dying of thromboembolic events including PE, stroke, and other forms of peripheral embolization. 49 An autopsy study in 152 patients with dilated cardiomyopathy revealed either pulmonary or systemic emboli or both in more than half of the patients. 50 …”
Section: Procoagulant State In Hfmentioning
confidence: 99%
“…A postmortem interrogation of implantable defibrillators in 83 patients with HF found that the prime mode of death was not an arrhythmia in 69% of the patients, with 16.9% dying of thromboembolic events including PE, stroke, and other forms of peripheral embolization. 49 An autopsy study in 152 patients with dilated cardiomyopathy revealed either pulmonary or systemic emboli or both in more than half of the patients. 50 …”
Section: Procoagulant State In Hfmentioning
confidence: 99%
“…Although many patients with ICDs eventually die from noncardiac causes, post hoc analyses have found ventricular tachycardia, ventricular fibrillation, and wide complex rhythms leading to electromechanical dissociation as a common cardiac cause of death. 24 Catheter ablation of ventricular tachycardia also remains an option in three clinical situations: (1) as adjunct to ICD, (2) as an alternative to ICD (if not a candidate), and (3) as prophylactic adjunctive therapy along with ICD. Providers may also prescribe wearable cardioverter-defibrillators, with trained nurses completing fittings of the devices in patients requiring temporary protection, or during bridging periods; survival rates seem similar to that of ICD patients.…”
Section: Arrhythmia Management and Heart Failurementioning
confidence: 99%
“…renal disease, ca. 20-30%) [55, 56]. Table 3. refers to the European Society of Cardiology (ESC) guidelines on decision making on implantable cardioverter defibrillator (ICD) implantation for secondary prevention of SCA due to severe arrhythmia [57, 58].…”
Section: Secondary Prevention Of Scamentioning
confidence: 99%